High-sensitivity troponin I in patients with rhabdomyolysis acutely intoxicated with psychotropic and chemical substances - Babulovska, Aleksandra; CHaparoska, Daniela; Pereska, Zanina; Simonovska, Natasha; Jurukov, Irena; Naumoski, Kiril; Kostadinoski, Kristin (Taylor & Francis, 2022)
Objective: We determine high-sensitivity troponin I (hs-Tnl) activity in patients with rhabdomyolysis following acute intoxication with psychotropic and chemical substances. Methods: This is a clinically controlled prospective study conducted in 2019 at the University Clinic of Toxicology in Skopje. In this study, 140 patients with rhabdomyolysis were divided into two groups depending on the intoxicating substance i.e. psychotropic or chemical. Rhabdomyolysis was defined according to the Poisoning Severity Score. High-sensitivity troponin (hs-TnI) was measured in all patients with rhabdomyolysis three times, on the first, third, and fifth days of hospitalization. Data were statistically analyzed in SPSS software, version 22.0 for Windows (SPSS, Chicago, IL, USA). Results: In all patients with rhabdomyolysis, the mean hs-TnI value on the first, third, and fifth days was 27.7 ± 78.3 mg/L, 43.7 ± 135.9 mg/L, and 28.73 ± 57.01 g/L, respectively. The comparison of hs-TnI in the three measurement times showed a significant difference (p ¼ 0.001). On the third day of hospitalization in all patients the hs-TnI was significantly higher compared to the fifth day (p ¼ 0.0001) as well as marginally insignificantly higher compared to the first day (p ¼ 0.057). The value of hs-TnI on the fifth day was insignificantly higher compared to the first day (p ¼ 0.021). We determined the highest values of hs-TnI in methadone intoxications (N ¼ 5, 279.7 ± 190.7 mg/L, other drugs (N ¼ 1, 138.4 mg/L); and benzodiazepines (N ¼ 3, 213.9 ± 232.5 mg/ L). Analysis by type of intoxication on the first, third, and fifth days showed that hs-TnI values were insignificantly higher in the psychotropic group compared with the chemical intoxication group. Conclusion: The value of hs-TnI was slightly higher in patients with rhabdomyolysis after acute psychotropic intoxication. Elevated levels of hs-TnI in psychotropic intoxications were likely related to the specific etiologies such as illicit substance use, while chemical intoxication was associated with the clinical outcome of intoxication.